Macrozoobenthic assemblages are associated with sediment organic matter across contrasting mangrove ecosystems of North Sumatra, Indonesia - ONRIZAL ONRIZAL; THEODORA LOUISA SIMBOLON; DITA ELISA PITRI SIDAURUK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Onrizal, Simbolon TL, Sidauruk DEP. 2026. Macrozoobenthic assemblages are associated with sediment organic matter across contrasting mangrove ecosystems of North Sumatra, Indonesia. Biodiversitas 27 (7): d270707. https://doi.org/10.13057/biodiv/d270707. Macrozoobenthic assemblages often respond quickly to changes in intertidal sediment, yet comparable evidence from North Sumatra, Indonesia, remains limited. We compared mangrove vegetation, macrozoobenthos, and measured sediment conditions in Sei Nagalawan, Belawan Sicanang, and Lubuk Kertang using a common station-based design. Each site contained three stations, each station contained three vegetation plots, and five macrozoobenthos quadrats were sampled within each plot. Across the nine stations, 1,543 individuals representing 17 species and four classes were recorded. Shannon diversity ranged from H': 1.321 to 2.454. Lubuk Kertang supported the widest observed species pool and the highest maximum diversity (14 species; H': 2.454), whereas Belawan Sicanang had the narrowest species pool (8 species). Sediment organic carbon showed the strongest positive station-level association with diversity (r: 0.851, p: 0.004), and clay showed a weaker positive trend (r: 0.658, p: 0.054). The first two PCA axes explained 78.05% of the total variation and contrasted clay-rich, organic-rich stations with warmer, sandier ones. Because the multivariate analyses were based on only nine stations, the correlation and ordination results are interpreted as exploratory rather than causal. Even so, the combined vegetation, sediment, and macrozoobenthos data show that benthic assemblages can strengthen biodiversity-based evaluation of mangrove condition and rehabilitation outcomes in North Sumatra.